Management Ideologies and Organizational Spirituality: a Typology - Pina e Cunha, Miguel (2019)
The topic of spirituality is gaining an increasing visibility in organization studies. It is our contention that every theory of organization is a theory of organizational spirituality. Based on Barley and Kunda’s 1992 Administrative Science Quarterly article, we discuss the evolution of management theories as spirituality theories. From such analysis, we suggest that there may be both a meaningful/liberating and an instrumental/exploitative side in the relationship between organizations and spirituality. Such a possibility is illustrated with a typology that advances four possible types of organizations regarding spirituality: the soulful organization, the holistic organization, the ascetic organization, and the professional organization. The expression of spirituality in each of these forms is discussed with the aim of contributing to a theoretically-based analysis of organizational spirituality.